Status and molecular genetic parameters of papillomavirus infection: individual characteristics and associative links with clinical and morphological factors of cervical cancer - L. S. Mkrtchian; V. I. Kiseleva; L. I. Krikunova; B. V. Boyko; V. R. Gusarova; G. P. Bezyaeva; L. V. Panarina; S. A. Ivanov; A. D. Kaprin; I. A. Zamulaeva (Южно-Российский онкологический журнал, 2024)
Purpose of the study. Study of the characteristics of human papillomavirus (HPV) infection, comparison of HPV status, molecular and genetic parameters of HPV high risk (HR) with the clinical and morphological characteristics of cervical cancer.Materials and methods. The study included 240 patients with morphologically verified cervical cancer stages I–III, in whom the presence of HPV DNA of 14 genotypes was examined before treatment; upon detection, viral load (VL), the presence and degree of DNA integration into the genome of the host cell were examined.Results. A number of statistically significant associative relationships have been identified between the molecular and genetic parameters of HPV infection and clinical and morphological indicators of the tumor process, in particular the relationship of HPV-negative CC with age and stage of the disease; HPV infection with several genotypes and HPV genotype – with the histological type of tumor; VL – with age, stage and histological type of tumor. Significant associative connections have been established between the molecular genetic parameters of the virus itself: genotype and level of VL, genotype and integration of HPV DNA into the host genome, as well as a negative linear correlation between VL and the degree of integration.Conclusion. The obtained data on the relationship between the molecular and genetic parameters of HPV infection and traditional prognostic factors can become the basis for further research on the development of prognostic models for the purpose of personalizing multimodal treatment programs.